On‐Cell NMR Contributions to Membrane Receptor Binding Characterization. Issue 6 (23rd June 2021) - Höfurthner, Theresa; Mateos, Borja; Konrat, Robert
Abstract: NMR spectroscopy has matured into a powerful tool to characterize interactions between biological molecules at atomic resolution, most importantly even under near to native (physiological) conditions. The field of in‐cell NMR aims to study proteins and nucleic acids inside living cells. However, cells interrogate their environment and are continuously modulated by external stimuli. Cell signaling processes are often initialized by membrane receptors on the cell surface; therefore, characterizing their interactions at atomic resolution by NMR, hereafter referred as on‐cell NMR, can provide valuable mechanistic information. This review aims to summarize recent on‐cell NMR tools that give information about the binding site and the affinity of membrane receptors to their ligands together with potential applications to in vivo drug screening systems. Abstract : On‐cell NMR combines the unique capacity to obtain atomic‐level information of biomolecules under the complex and changing conditions found in and on living cells with the high sensitivity to detect small changes in the chemical shift of NMR‐active nuclei to their chemical environment, which gives particular information about the binding kinetics. Additionally, binding site mapping is achieved by measuring specific NMR experiments described in this review. Furthermore, strategies for sample preparation and how to monitor the cell's lifetime are described.